The Correlation Analysis for New Media Internet Celebrity Economy in College Students’ Entrepreneurial Values and Entrepreneurial Behavior - Xiang, Yonghui; Wang, Weiwei (Frontiers in Psychology, 2022)
Driven by the development of new media, the Internet celebrity economic marketing model has gradually become one of the mainstream online marketing models. It has aroused warm attention on the network platform and provided a breakthrough for entrepreneurship for college students. This thesis aims to explore the influence of the Internet celebrity economy on college students’ entrepreneurial values and entrepreneurial behavior. A questionnaire is conducted among students in two colleges in Xi’an. Moreover, a theoretical model is constructed according to the influence principle of entrepreneurial values on entrepreneurial behavior. The reliability and validity of the questionnaire data are analyzed, and the mediating and moderating effects are tested. The results of the questionnaire show that contemporary college students generally pay attention to Internet celebrity mainly through live broadcast platforms and shopping platforms, among which entertainment and shopping account for the largest proportion. More than 40% of college students are optimistic about the impact of Internet celebrity economy and remain rational and objective on the whole. The results of model analysis show that the standardized path coefficient of entrepreneurial values on entrepreneurial behavior reaches a significant level of 0.85, and entrepreneurial values have a positive and significant impact on entrepreneurial behavior. The influence coefficient of the Internet celebrity economy on entrepreneurial intention is 0.79, and the influence coefficient of entrepreneurial intention on entrepreneurial behavior is 0.84, both reaching a significant level. The entrepreneurial intention has an incomplete intermediary effect in the influence mechanism of the Internet celebrity economy on entrepreneurial behavior. The chain double intermediary composed of entrepreneurial motivation and entrepreneurial intention has an incomplete intermediary effect in the indirect impact path of the Internet celebrity economy on entrepreneurial behavior. The influence coefficient of the product of entrepreneurial intention and entrepreneurial policy satisfaction on entrepreneurial behavior is 0.17, which is always greater than −12.28, indicating that entrepreneurial policy satisfaction has a regulatory effect in the impact path of entrepreneurial intention on entrepreneurial behavior. The research results can guide college students to view the Internet celebrity economy rationally and objectively, and provide some guidance for them to have correct entrepreneurial values.